Strategi Manajemen Perencanaan dan Pengorganisasian The Room 19 - Annisa, Annisa Apriyanti; Erwina, Wina; Perdana, Fitri (Literatify : Trends in Library Developments, 2025)
The library café concept introduces innovation in the library world by creating a more modern and comfortable atmosphere. This study aims to analyze the management strategies in planning and organizing The Room 19 as a library café. This research employs a qualitative method with a case study approach, using observation, interviews, documentation, and literature review as data collection techniques. Data analysis is conducted through data reduction, data presentation, and verification. The findings indicate that The Room 19’s planning strategy involves environmental analysis, vendor involvement in interior design, and the establishment of a concept inspired by To Room Nineteen, a book by Doris Lessing. The organizational strategy includes forming a structured team consisting of Co-Founder & Management and Library Monitor, with a monthly shift division system. The Room 19 implements an online reservation system via Instagram and schedules visits into three daily shifts, each lasting four hours. Additionally, collaborations with various brands and communities support product offerings and regular activities, while the Opaper application is used for online book borrowing and product transactions. These strategies ensure efficient management and enhance the appeal of the library café.